An fMRI study of mesial temporal lobe epilepsy with different pathological basis using amplitude of low-frequency fluctuation analysis - Wei WEI; Zhi-qiang ZHANG; Qiang XU; Yu-bin HUANG; Guang-ming LU; Qi-fu TAN (Chinese Journal of Contemporary Neurology and Neurosurgery, 2014)
Objective To study the distinction of abnormal brain activity in mesial temporal lobe epilepsy (mTLE) with hippocampal sclerosis (HS) or other pathogical basis, and to discuss their underlying pathophysiological mechanism in mTLE.  Methods Thirty mTLE patients with unilateral hippocampal sclerosis (mTLE-HS) and 30 mTLE patients with occupying lesion in unilateral temporal lobe (mTLE-OL) were investigated by comparing with 30 age- and sex-matched healthy subjects. MRI data were collected using a Siemens 3.0T scanner, and all of the participants were studied using amplitude of low-frequency fluctuation (ALFF) analysis of resting state fMRI. A cost-function modification was used for image preprocessing, then the difference of extratemporal mALFF changes between the two groups of mTLE patients were analyzed with two-sample t test, and the correlation between mALFF and epilepsy duration of mTLE were also investigated.  Results In the resting state, mTLE-HS patients and mTLE-OL patients all showed significant changes in mALFF in extratemporal structures, but the distribution patterns of changes in brain were different. Compared with mTLE-HS, the mTLE-OL patients showed increased mALFF in bilateral inferior parietal lobes, precuneus, angular gyrus, middle and posterior cingulate gyrus and contralateral middle temporal gyrus, while mALFF reducing was observed in contralateral postcentral gyrus, bilateral middle occipital gyrus and cerebellum (P < 0.05, AlphaSim corrected), that is to say, the default mode network (DMN) in mTLE-HS were inhibited more seriously than in mTLE-OL patients. Correlation analysis showed that no significant correlation was found between mALFF and epilepsy duration in mTLE-HS patients; mALFF in bilateral middle and posterior cingulate gyrus was positively correlated with epilepsy duration in mTLE-OL patients (r = 0.687, P = 0.000), while mALFF in bilateral anterior cingulate gyrus was negatively correlated with epilepsy duration (r = -0.621, P = 0.000).  Conclusions mTLE with different pathological basis showed different distribution patterns of abnormal brain function, which indicated that their latent pathophysiological mechanism might be different, further confirming mTLE-HS was a specific type of epilepsy.   doi: 10.3969/j.issn.1672-6731.2014.11.008